Impact of COVID-19 on Egypt’s dairy and artichoke value-chains: Qualitative findings from rapid value chain assessments - Abdelaziz, Fatma; Abay, Kibrom A.; El-Enbaby, Hoda; Breisinger, Clemens; Kurdi, Sikandra (International Food Policy Research Institute, 2021)
The COVID-19 crisis is having strong impacts on the Egyptian economy, but these impacts differ strongly across sectors.1 Based on scenarios run using a Social Accounting Matrix (SAM) multiplier model of Egypt’s economy, COVID-19 is estimated to have resulted in an 8.6 percent decline in Egypt’s GDP during the 4th quarter of FY 2019/20 (April to June). The services sector was hit hardest, falling by 10.9 percent, followed by industry, which contracted by 8.3 percent. Agriculture was the most resilient sector, although there are large differences in the relative impact of COVID across agricultural subsectors.